(untitled) (Al-Aasar, 2025)
This critical analytical study aims to examine the standards of cohesion, intentionality, acceptability, and informativity in Yahya al-Sinwar’s novel “Thorns and Carnations” through a linguistic–pragmatic approach that views the text as an interactive entity shaped by both authorial intent and social context. The research explores how textual cohesion is achieved through the interconnection of sentences, narrative events, and characters, and how intentionality guides meaning to express the author’s ideological and political consciousness. It also investigates the standard of acceptability in relation to the reader’s cultural expectations, and the standard of informativity as a means of producing new knowledge and enriching collective awareness. The study concludes that al-Sinwar skillfully employs these textual standards to create a balanced narrative that harmonizes linguistic structure with thematic depth. “Thorns and Carnations” thus emerges as a rich and intellectually engaging literary text that combines aesthetic expression with national consciousness, reflecting the spirit of resistance and the human quest for freedom and identity.